A Mediterranean diet plan in lactating women with obesity reduces maternal energy intake and modulates human milk composition – a feasibility study - Sims, Clark R.; Saben, Jessica L.; Martinez, Audrey; Sobik, Sarah R.; Crimmins, Meghan R.; Bulmanski, Jessica E.; Turner, Donald; Furst, Annalee; Jansen, Lisa T.; Bode, Lars; Andres, Aline (Frontiers in Nutrition, 2024)
Maternal obesity is associated with increased concentrations of human milk (HM) obesogenic hormones, pro-inflammatory cytokines, and oligosaccharides (HMOs) that have been associated with infant growth and adiposity. The objective of this pilot study was to determine if adherence to a Mediterranean meal plan during lactation modulates macronutrients and bioactive molecules in human milk from mothers with obesity. Sixteen healthy, exclusively breastfeeding women with obesity (body mass index ≥ 30 kg/m2) enrolled between 4 and 5 months postpartum. The women followed a 4-week Mediterranean meal plan which was provided at no cost. Maternal and infant anthropometrics, HM composition, and infant intakes were measured at enrollment and at weeks 2 and 4 of the intervention. Thirteen mother-infant dyads completed the study. Additionally, participants from an adjacent, observational cohort who had obesity and who collected milk at 5 and 6 months postpartum were compared to this cohort. Participants’ healthy eating index scores improved (+27 units, p < 0.001), fat mass index decreased (-4.7%, p < 0.001), and daily energy and fat intake were lower (-423.5 kcal/day, p < 0.001 and -32.7 g/day, p < 0.001, respectively) following the intervention. While HM macronutrient concentrations did not change, HM leptin, total human milk oligosaccharides (HMOs), HMO-bound fucose, Lacto-N-fucopentaose (LNFP)-II, LNFP-III, and difucosyllacto-N-tetrose (DFLNT) concentrations were lower following the intervention. Infant intakes of leptin, tumor necrosis factor (TNF)-α, total HMOs, HMO-bound fucose, LNFP-III and DFLNT were lower following the intervention. Specific components of the maternal diet (protein and fat) and specific measures of maternal diet quality (protein, dairy, greens and beans, fruit and vegetables) were associated with infant intakes and growth. Adherence to a Mediterranean meal plan increases dietary quality while reducing total fat and caloric intake. In effect, body composition in women with obesity improved, HM composition and infants’ intakes were modulated. These findings provide, for the first time, evidence-based data that enhancing maternal dietary quality during lactation may promote both maternal and child health. Longer intervention studies examining the impact of maternal diet quality on HM composition, infant growth, and infant development are warranted.